Wireless structural health monitoring (SHM) system for damage detection using ultrasonic guided waveform response - Shirazi, A. H. S.; Muda, M. K. H.; Thirumurthy, M. J.; Mustapha, Faizal (Universiti Putra Malaysia Press, 2017)
This paper presents an improved version of a wireless device embedded with a smart PZT sensor to detect flaws and structural defects on selected investigated structure. Smart PZT sensors were used as an actuator and sensor, coupled with two XBee's and one signal generator IC chip. Programme execution on transmitting and receiving the ultrasonic guided wave via the PZT sensor had been written in MATLAB. The developed source code is basically to receive serial data from one Xbee to another remote Xbee attached to the investigated structural system. The refined waveform response is utilised for prognosis of the true structural status. The 4-mm simulated holed into one of the aluminium structural plate is benchmarked with its pristine condition in validating the effectiveness of the developed SHM wireless module. Results showed that the wave is more even in non-defected area and disrupted in affected area. Ultrasonic waves increase continuously for non-destructive evaluation and structural health monitoring in various structural applications because the guided wave can propagate long distances and reach difficult-to-access regions; for inspecting porous and some non-porous materials ultrasonic waves attenuate fast and are very useful. Recent advances in ultrasonic wave application model and results are discussed in this paper.